IMF-supported programs in capital account crises - Ghosh, Atish R. (Washington, DC : International Monetary Fund, 2002)
This paper examines the design and experience of IMF supported plans in the context of eight capital account crises during the 1990's in the following countries: Turkey, Mexico, Argentina, Thailand, Indonesia, Korea, the Philippines and Brazil. The paper focuses on the financing strategies adopted and the role of macroeconomic and structural policies.
Includes bibliographical references (p. 90-92).
oif 27/04/15
Loan
Keywords: International Monetary Fund -- Developing countries; Financial crises -- Developing countries; Crisis management -- Developing countries; Balance of payments -- Developing countries; Capital movements -- Developing countries